Case Report: Changes of Vascular Reactivity and Arterial Stiffness in a Patient With Covid-19 Infection - Jud, Philipp; Kessler, Harald H.; Brodmann, Marianne (Frontiers in Cardiovascular Medicine, 2021)
Covid-19 infection may be associated with a higher incidence developing cardiovascular complications, however, the underlying mechanisms contributing to cardiovascular complications are largely unknown, while endothelial cell damage may be present. We want to report a 24-year-old woman with Covid-19 infection who had undergone measurements of vascular reactivity and arterial stiffness, including flow-mediated dilation (FMD), nitroglycerin-mediated dilation (NMD), aortic pulse wave velocity (PWV), augmentation index and carotid intima-media-thickness (cIMT) at the time when Covid-19 was diagnosed. Reduced FMD of 0.0% and NMD of 15.5% were observed, while PWV (5.9m/sec), Aix (27%) and cIMT with 0.4mm of both common carotid arteries were unremarkable. Repeated measurements of FMD, NMD, PWV, Aix and cIMT six weeks after Covid-19 infection revealed persistently reduced FMD (0.0%), while NMD (17.24%), PWV (5.6m/sec) and augmentation index (13%) ameliorated. This case suggests potential impact of covid-19 infection on endothelial function, also in young Covid-19 patients without any comorbidity.